Baraya Ngajaga Intervention: Promoting Bystander Behavior for Bullying Prevention Through Sundanese Cultural Values in Junior High School Students - Maslihah, Sri; Mudin, Muhammad Ilham; Nurendah, Gemala; Hidayat, Ghinaya Ummul Mukminin; Lestari, Selfiyani (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2026)
This study was conducted to develop and examine a bystander intervention programme integrated with Sundanese values for preventing bullying amongst junior high school students, namely the Baraya Ngajaga programme. The research utilized a quasi-experimental design employing One-Group Pretest-Posttest Design, which was carried out at SMPN X Bandung, Indonesia, involving ten female students aged 13-14 years from the school's